2024
DOI: 10.1029/2023gl107221
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Sea Ice Loss Modulates the Surface Impact of Autumn Stratospheric Polar Vortex Stretching Events

Chuntao Zou,
Ruonan Zhang

Abstract: The cold Eurasia has been proposed to be closely linked to the weakening of the stratospheric polar vortex (SPV), however, how the Arctic sea ice modulates the surface impacts of the weak SPV is unclear. This study explores the critical modulating role of reduced Arctic sea ice in the surface cooling response to SPV stretching events in autumn. Here, through ERA5 reanalysis and Whole Atmosphere Community Climate Model simulations, we show that Eurasian cold events are more likely (45%) to occur in days 30–50 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…Our analysis has demonstrated that the surface signature of strong stratospheric wave events and the associated cold extreme risk over North America depends on the phase of the QBO. In this regard, while a few studies have shown that downward wave reflection is susceptible to SST, solar activity, and sea ice (Lubis et al 2016, Lu et al 2017, Zou and Zhang 2024, much work is needed to understand the sensitivity of extreme stratospheric wave activity to various factors of climate variability. Findings from our paper could potentially enhance forecasting of severe winter cold in the U.S. and Canada, benefiting transportation, energy management, and public health by enabling better preparedness and resource allocation (Vajda et al 2014, Perera et al 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis has demonstrated that the surface signature of strong stratospheric wave events and the associated cold extreme risk over North America depends on the phase of the QBO. In this regard, while a few studies have shown that downward wave reflection is susceptible to SST, solar activity, and sea ice (Lubis et al 2016, Lu et al 2017, Zou and Zhang 2024, much work is needed to understand the sensitivity of extreme stratospheric wave activity to various factors of climate variability. Findings from our paper could potentially enhance forecasting of severe winter cold in the U.S. and Canada, benefiting transportation, energy management, and public health by enabling better preparedness and resource allocation (Vajda et al 2014, Perera et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is the role of the stratosphere (Kolstad et al 2010, Yu et al 2015, Cohen et al 2021, Huang et al 2021, Davis et al 2022. There is increasing evidence that extreme stratospheric wave variability contributes to surface cold waves through planetary wave reflection (Shaw and Perlwitz 2013, Kretschmer et al 2018, Cohen et al 2021, Liang et al 2022, Messori et al 2022, Millin et al 2022, Reichler and Jucker 2022, Shen et al 2022, Zou et al 2023, Zou and Zhang 2024. Using observations and climate models, Ding et al (2023b) demonstrate that strong stratospheric wave activity is followed by changes in the vertical coupling of planetary waves, with an increased risk of cold extremes over North America.…”
Section: Introductionmentioning
confidence: 99%